Akuntabilitas Dalam Akuntansi dan Pelaporan Keuangan Pondok Pesantren di Indonesia - Ahmad Baehaqi; Nida Faradila; Lutfi Zulkarnain (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2021)
This The purpose of this study is to analyze the implementation of accountability in accounting and financial reporting implemented by the Darunnajah Islamic Boarding School (PPDN). This study uses descriptive qualitative with a case study approach giving semi-structured interviews to key informants, observation and inquiry of supporting documents/evidence. Besides the interviews, this study also uses secondary data obtained from literature studies. The study indicates that the implementation of accountability in PPDN accounting and financial reporting have been running quite well, but still needs improvement. The finance department at PPDN does not have an accounting/finance background and is in charge of recording cash / bank transfers through the Darunnajah Smart System and B-Ware application systems. The financial statements are prepared by PPDN internal auditors with accounting backgrounds with reference to PSAK 45.